Beliefs of Torajanese Pregnant Mother - Komariah, Euis Dedeh; Sili Beda, Nikodemus; Situngkir, Rosmina; Novia, Kristia (Babali Nursing Research, 2024)
Introduction: Various factors impact the health of pregnant women, including access to healthcare facilities and a nutritious diet. Cultural norms and beliefs prevalent in Indonesian society may influence food consumption patterns. This study explores dietary restrictions and preferred food choices during pregnancy among Toraja ethnic pregnant women.Methods: Employing a qualitative research methodology, specifically a descriptive phenomenological approach, this study was conducted within the jurisdiction of the Ge'tengan Community Health Center, Mengkendek District, Tana Toraja, Indonesia. The research adopted purposive sampling, involving eight pregnant women as participants. Data was collected through individual interviews, lasting 45 to 60 minutes for each participant.Results: The findings revealed three overarching themes: prohibited foods during pregnancy, reduced staple food intake, and the influence of elders on dietary practices and beliefs.Conclusion: Leveraging traditional wisdom regarding dietary recommendations can serve as valuable input in designing nutritional education programs tailored to meet the needs of Toraja ethnic pregnant women. Meanwhile, there are some foods that mothers need as support in fulfilling nutrition, and this is contrary to health. Therefore, it is very important to raise public awareness by disseminating accurate information about nutrition for pregnant women in the Toraja tribe by maintaining culture if it is not contrary to health, then helping people to adapt to cultures that benefit health called negotiation, and changing or replacing culture if the culture or habit is detrimental.